Perceived Stigma, Psychological Response, and Nurse Coping In The Covid-19 Pandemic In Indonesia - Fitria Endah Janitra; Erna Melastuti; Ah Yusuf; Harif Fadhilah; Yan Adi Wibawa (Jurnal Keperawatan Padjadjaran, 2021)
Nurses are at the forefront of being directly involved in the care of Covid-19 patients. This can put nurses in a difficult position, especially if they had lack support from the surrounding environment. The society’s negative stigma towards nurses can trigger psychological problems for them. Good coping is needed to maintain the work performance of nurses. This study aims to identify the perceived stigma, psychological response, and coping of nurses involved in caring for Covid-19 patients in Indonesia. This research was a cross-sectional study based on an electronic survey. The number of respondents was 509 nurses who came from all regions in Indonesia on 11–20 April 2020. Respondents were nurses who handled Covid-19 patients directly. The data were collected using a modified questionnaire the Berger stigma scale, DASS and Brief of Cope with a total of 27 questions. The questionnaires used have been proven valid and reliable after being tested on 30 nurses treating Covid-19 patients with a Cronbach Alpha value as follows: modified Berger Stigma Scale 0.952; modified DASS 0.928; and modified Brief of Cope 0.753. Most respondents were 26-35 years old (52.1%), female (61.5%), and worked in government-owned hospitals (48.3%). 231 respondents were stigmatized (45.4%), 274 respondents were depressed (46.2%) and 209 respondents experienced stress (41.1%). The majority of respondents chose problem focused coping (65.8%). This study shows that some respondents feel they were stigmatized by society, but they have good coping (problem focused coping) to reduce their mental burden. Negative stigma against nurses is often difficult to avoid. Support from family and colleagues was something that can ease the mental burden of nurses. Support from the government was needed to educate the public so that it does not give negative stigma to nurses and other health workers.